The Aral Sea Basin Water for Sustainable Development in Central Asia - Xenarios, Stefanos; Schmidt-Vogt, Dietrich; Qadir, Manzoor; Janusz-Pawletta, Barbara; Abdullaev, Iskander (Taylor & Francis, 2019)
This book offers the first multidisciplinary overview of water resources issues and management in the Aral Sea Basin, covering both the Amu Darya and Syr Darya River Basins. The two main rivers of Amu Darya and Syr Darya and their tributaries comprise the Aral Sea Basin area and are the lifeline for about 70 million inhabitants in Central Asia. Written by regional and international experts, this book critically examines the current state, trends and future of water resources management and development in this major part of the Central Asia region. It brings together insights on the history of water management in the region, surface and groundwater assessment, issues of transboundary water management and environmental degradation and restoration, and an overview of the importance of water for the key economic sectors and overall socio-economic development of Central Asian countries, as well as of hydro politics in the region. The book also focusses on the future of water sector development in the Basin, including a review of local and international actors, as well as an analysis of the current status and progress towards the Sustainable Development Goals by Basin countries. The book will be essential reading for those interested in sea basin management, environmental policy in Central Asia and water resource management more widely. It will also act as a reference source for decision-makers in state agencies, as well as a background source of information for NGOs.